2019
DOI: 10.1002/jhet.3642
|View full text |Cite
|
Sign up to set email alerts
|

XtalFluor‐E: An Efficient Reagent for Synthesis of Oxazolines from Carboxylic Acids and O‐Silylated Amino Alcohols

Abstract: An efficient protocol has been developed for the synthesis of 2‐oxazolines from carboxylic acids and silylated amino alcohols. The advantage of this method was demonstrated by preparing O‐silylated amino alcohols. The reaction proceeds via in situ desilylation of O‐silylated amide followed by cyclization. Studies on silyl deprotection were carried out to explain yield for 2‐oxazolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Oxazoline and their derivatives have been found to have pharmacological activities 14 , anticancer activity 15,16 antibacterial, antitumor, antidepressant, and anti-Alzheimer's activities. [17][18][19][20][21][22][23] The antioxidant properties of aryl-substituted 2-oxazolines have recently been investigated. [24][25][26] Our present In-silico studies of 2-aryloxazoline compounds which were synthesized and showed the antifungal activity with low cytotoxicity by Luis M. Z. Argomedo, and et al (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Oxazoline and their derivatives have been found to have pharmacological activities 14 , anticancer activity 15,16 antibacterial, antitumor, antidepressant, and anti-Alzheimer's activities. [17][18][19][20][21][22][23] The antioxidant properties of aryl-substituted 2-oxazolines have recently been investigated. [24][25][26] Our present In-silico studies of 2-aryloxazoline compounds which were synthesized and showed the antifungal activity with low cytotoxicity by Luis M. Z. Argomedo, and et al (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%